Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1016/j.ijsu.2013.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Head injury triage in a sub Saharan African urban population

Abstract: In a resource limited setting, basic trauma tools such as GCS and heart rate can effectively triage head injury patients, who comprise the most critically ill trauma patients. Improvements in head injury outcome require multifaceted efforts including the development of a trauma system to improve pre-hospital care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 25 publications
3
29
0
Order By: Relevance
“…GCS was developed to categorise head injury in the 1970 s and still is widely used in over 80 countries for prognosis and research [5] . A recent study in Malawi confirmed the usefulness of GCS as a mortality marker in a resource limited setting [16] . Amongst PMH EC HI patients who had a GCS recorded; 6% were severe, 10% moderate and the remainder mild.…”
Section: Discussionmentioning
confidence: 87%
“…GCS was developed to categorise head injury in the 1970 s and still is widely used in over 80 countries for prognosis and research [5] . A recent study in Malawi confirmed the usefulness of GCS as a mortality marker in a resource limited setting [16] . Amongst PMH EC HI patients who had a GCS recorded; 6% were severe, 10% moderate and the remainder mild.…”
Section: Discussionmentioning
confidence: 87%
“…[ 3 ] In sub-Saharan Africa, there is a paucity of accurate trauma data on the contribution of head injury to trauma-related mortality. [ 4 ] However, sub-Saharan Africa demonstrates a higher head injury-related rate varying from 150 to 170/100,000, respectively, due to motor vehicle crashes compared to a global rate of 106/100,000. [ 5 ] A cross-sectional hospital-based study in Nigeria reported that 31% of all trauma deaths were attributable to severe head injury.…”
Section: Introductionmentioning
confidence: 99%
“…Pre-hospital care Care details included first aid and pre-hospital assessment, transport time, mode of arrival [ 25 , 29 , 37 , 39 , 40 ] 3. Injury event information Date and time of injury, place and activity of injury [ 4 , 23 26 , 28 43 ] 4. Emergency room assessment and treatment Vital signs, GCS, pre-existing conditions, suspicion of alcohol and substance use, lab and radiology investigations, patient management, respiratory support, ED disposition [ 4 , 23 , 25 37 , 39 , 41 ] 5.…”
Section: Main Textmentioning
confidence: 99%